PEER COUNSELING TO INCREASE SELF-EFFICACY OF STUDENTS WHO EXPERIENCE BROKEN HOMES - Susgaleni, Firstalenda; Ridlwan , Muhamad Khoiri (LP2M IAI Al-Khairat Pamekasan, 2024)
A broken home has a tremendous impact on children, particularly on their psychology and daily life. The effects that arise include disappointment, difficulty in trusting others, disbelief in marriage, trauma, and low self-efficacy. Low self-efficacy is manifested by a lack of motivation to study, disbelief in one's abilities, inability to distinguish between right and wrong, and difficulty making decisions. The subjects of this research were 3 students from UIN Sayyid Ali Rahmatullah Tulungagung, all of whom shared the same background of being from broken homes. They felt almost the same, including feelings of neglect, disappointment, lack of motivation, and inability to discern what is good and right for themselves. The subjects participated in peer counseling services provided by the campus and felt better because their opinions were listened to without judgment. Therefore, peer counseling is very helpful in improving self-efficacy in students.